2019
DOI: 10.12968/bjon.2019.28.sup14a.s16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences of using ports and non-coring needles

Abstract: The following case studies describe the use of the Smith Medical implanted ports and Gripper huber needles. Smiths Medical produces a range of implanted ports that include the Port-A-Cath and P.A.S. Port Power P.A.C. systems. The ports are easy to implant, maintain and remove. They are lightweight and have features that are designed to reduce complication rates, including a highly compressed septum to increase needle retention, a titanium chamber with a gouge-resistant floor, a bevelled chamber for optimal rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Our review on sample sizes found that two sample sizes were not specified, 28,30 six sample sizes were not applicable, 11,24–27,29 four sample sizes had under 50 patients, 14,17,21,31 three had sample sizes between 50 and 100 patients, 15,19,23 one was between 100 and 500 patients, 16 two were between 500 and 1000 patients 18,20 and two were over 1000 patients. 22,32…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Our review on sample sizes found that two sample sizes were not specified, 28,30 six sample sizes were not applicable, 11,24–27,29 four sample sizes had under 50 patients, 14,17,21,31 three had sample sizes between 50 and 100 patients, 15,19,23 one was between 100 and 500 patients, 16 two were between 500 and 1000 patients 18,20 and two were over 1000 patients. 22,32…”
Section: Resultsmentioning
confidence: 95%
“…The most common research questions examined by the reports were infection of VADs with 30% ( n = 6) of them being related to this topic, 15,17,20,23,24,28 25% ( n = 5) reported on the care and maintenance of VADs for Health Care Practitioners (HCPs), 14,21,25,26,27 20% ( n = 4) reported on complications associated with VADs, 11,22,29,32 10% ( n = 2) reported on complications of a peripherally inserted central catheter (PICC) in haematology patients, 16,19 10% ( n = 2) reported on education for parents of paediatric patients 18,30 and 5% ( n = 1) reported on VAD choice by the patient. 31…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations